User Interface (UI) Discovery Application To Measure Query Accuracy On Interface Repository - Shofiyatun Najah; Muhammad Ainul Yaqin; Linda Salma Angreani; Abd. Charis Fauzan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2019)
SaaS (Software as a Service) application has many architecture layers, those are: data layer, service layer, process layer, and UI layer. UI layer is a GUI layer which has function to prepare the interface both system and user receiving input from user and show back to user. This research tells about how to build user interface (UI) discovery as a part of software based on SaaS. The aim of this application is to make easier user for finding user interface which appropriate needed configuration. This UI discovery application is developed by using ontology theory, those are RDF map and query SPARQL. The working way of UI discovery is entering the keywords which contain form name, or component details needed. UI discovery will search based on the entering keywords automatically. The trials will use two search models, those are data search and detail search. The calculation result of those both trials are from recall score 95%, accuracy score 100%, and precision score with different percentage. The percentage of data search model is 95%, while on detail search model is 90%. Those differences found because of some of irrelevant document found on detail search and netted query. Therefore, on data search shows that the result is more relevant and shows the better of system's prosperity. Keywords : Software as a service; discovery; query accuracy; interface repository